2012
DOI: 10.1111/j.1476-5381.2012.02126.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel pyrazole compounds for pharmacological discrimination between receptor‐operated and store‐operated Ca2+ entry pathways

Abstract: Background and purposePyrazole derivatives have recently been suggested as selective blockers of transient receptor potential cation (TRPC) channels but their ability to distinguish between the TRPC and Orai pore complexes is ill-defined. This study was designed to characterize a series of pyrazole derivatives in terms of TRPC/Orai selectivity and to delineate consequences of selective suppression of these pathways for mast cell activation.Experimental approachPyrazoles were generated by microwave-assisted syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
154
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(162 citation statements)
references
References 54 publications
5
154
3
Order By: Relevance
“…Pyr3 also inhibits SOCE due to Orai-1, at concentrations close to that for TRPC3 (our data and ref. 19), raising concerns regarding its selectivity. Selective TRPC6 inhibitors were recently reported by Urban et al (25) using the Chembionet library; however, their IC 50 for channel blockade ranged from 3 to 15 μM, and no assessment of hypertrophic modulation was reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyr3 also inhibits SOCE due to Orai-1, at concentrations close to that for TRPC3 (our data and ref. 19), raising concerns regarding its selectivity. Selective TRPC6 inhibitors were recently reported by Urban et al (25) using the Chembionet library; however, their IC 50 for channel blockade ranged from 3 to 15 μM, and no assessment of hypertrophic modulation was reported.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors such as SKF-96365, 2-aminoethoxydiphenyl borate (14), and spider venom GsMTx-4 (15) are nonselective. Pyr3 (ethyl-1-(4-(2,3,3-trichloro-acryl-amide)phenyl)-5-(trifluoromethyl)-1H-pyrazole-4-carboxylate) has been identified as a selective TRPC3 antagonist (16,17), although members of the 5-(trifluoro-methyl)-1H-pyrazole family to which it belongs block Ca 2+ release-activated calcium (CRAC) channels, such as Orai channels (18,19).…”
Section: Significancementioning
confidence: 99%
“…A pyrazole-derivative compound is also reported to inhibit SOCs as well as TRPC3 [ 169 ], but our fi ndings strongly suggest that a pyrazole-derivative compound (especially Pyr3) will become a promising seed for the treatment of chronic heart failure. …”
Section: Resultsmentioning
confidence: 78%
“…Some ryrazole derivatives have recently been suggested to be relatively selective blockers for TRPC channels (Schleifer et al, 2012). In WT mice, we showed that Pyr10, blocked the membrane depolarization of SAN cause by Ang II and attenuated the increase in pacemaker firing rate induced by Ang II (Figure 5).…”
Section: Trpc3 and Sino-atrial Arrhythmiasmentioning
confidence: 67%
“…Pyr3, a pyrazole derivative, has been suggested to be a blocker of TRPC3 (Kiyonaka et al, 2009) but it inhibits Orai1 mediated SOCE with similar potency (Salmon and Ahluwalia, 2010). Recently, a new selective blocker of TRPC3-ROCE blocker, Pyr10 has been developed and it displayed substantial selectivity for TRPC3-ROCE mediated responses over Orai1 mediated SOCE (Schleifer et al, 2012). We therefore studied the effect of Pyr10 on pacemaking and intracellular Ca 2+ after application of Ang II and/or the DAG derivative, OAG.…”
Section: Evidence Trpc3 Is Involved In Roce In Intact Mouse Sinoatriamentioning
confidence: 99%